The best of both worlds: a hybrid approach for optimal pre- and intraoperative identification of sentinel lymph nodes - KleinJan, G. H.; van Werkhoven, E.; van den Berg, N. S.; Karakullukcu, M. B.; Zijlmans, H. J. M. A. A.; van der Hage, J. A.; van de Wiel, B. A.; Buckle, T.; Klop, W. M. C.; Horenblas, S.; Valdés Olmos, R. A.; van der Poel, H. G.; et al. (European journal of nuclear medicine and molecular imaging, 2018)
Purpose Hybrid image-guided surgery technologies such as combined radio- and fluorescence-guidance are increasingly gaining interest, but their added value still needs to be proven. In order to evaluate if and how fluorescence-guidance can help realize improvements beyond the current state-of-the-art in sentinel node (SN) biopsy procedures, use of the hybrid tracer indocyanine green (ICG)- 99m Tc-nancolloid was evaluated in a large cohort of patients. Patients and methods A prospective trial was conducted (n = 501 procedures) in a heterogeneous cohort of 495 patients with different malignancies (skin malignancies, oral cavity cancer, penile cancer, prostate cancer and vulva cancer). After injection of ICG- 99m Tc-nanocolloid, SNs were preoperatively identified based on lymphoscintigraphy and SPECT/CT. Intraoperatively, SNs were pursued via gamma tracing, visual identification (blue dye) and/or near-infrared fluorescence imaging during either open surgical procedures (head and neck, penile, vulvar cancer and melanoma) or robot assisted laparoscopic surgery (prostate cancer). As the patients acted as their own control, use of hybrid guidance could be compared to conventional radioguidance and the use of blue dye ( n = 300). This was based on reported surgical complications, overall survival, LN recurrence free survival, and false negative rates (FNR). Results A total of 1,327 SN-related hotspots were identified on 501 preoperative SPECT/CT scans. Intraoperatively, a total number of 1,643 SNs were identified based on the combination of gamma-tracing (>98%) and fluorescence-guidance (>95%). In patients wherein blue dye was used ( n = 300) fluorescence-based SN detection was superior over visual blue dye-based detection (22–78%). No adverse effects related to the use of the hybrid tracer or the fluorescence-guidance procedure were found and outcome values were not negatively influenced. Conclusion With ICG- 99m Tc-nanocolloid, the SN biopsy procedure has become more accurate and independent of the use of blue dye. With that, the procedure has evolved to be universal for different malignancies and anatomical locations.